Yours is the night - Dykes, Amanda (Bethany House, a division of Baker Publishing Group, 2021)
"Mireilles finds her world rocked when the Great War comes crashing into the idyllic home she has always known, taking much from her. When Platoon Sergeant Matthew Petticrew discovers her in the Forest of Argonne, three things are clear: she is alone in the world, she cannot stay, and he and his two companions might be the only ones who can get her to safety"--